Numerical modelling of elastic modulus and diffusion coefficient of concrete as a three-phase composite material. (20th November 2018) - Liu, Cheng; Xie, Deqing; She, Wei; Liu, Zhiyong; Liu, Guojian; Yang, Lin; Zhang, Yunsheng
Highlights: The various regular- and irregular-shaped aggregates are constructed using a pixel-based method. The effects of aggregate characteristics on elastic and diffusive properties of concrete are investigated. The aggregate characteristics apart from the aggregate type, play a slight role in the elastic properties of concrete. The aggregates characteristics have a significant influence on the diffusive properties of concrete. Abstract: Concrete is a complex three-phase composite material at a mesoscale, thus its overall elastic and diffusive properties strongly depend on that of each component. However, the effects of aggregate characteristics are little considered, especially the aggregate shape effect. In this study, a set of numerical methods is employed to evaluate the effects of aggregate characteristics on the elastic and diffusive properties of concrete. Firstly, a concrete representative volume element (RVE) is constructed using a pixel-based method by packing aggregates surrounding a soft interlayer as ITZ in a homogeneous mortar matrix. The different aggregate characteristics including morphology, fineness and type, are respectively considered. Subsequently, a set of the finite element-based and finite difference-based numerical method that is designed for the pixel-based concrete structure, is applied to predict the elastic modulus and the diffusion coefficient of concrete. The simulated results indicate that aggregate characteristics apart from aggregate type play a negligible role in the elastic modulus of concrete, while the effects of aggregate characteristics on the diffusion coefficient of concrete are pronounced. The aggregates with less regularity or coarser size can decrease the diffusion coefficient of concrete. Furthermore, the property of ITZ is another pronounced factor for the elastic and diffusive properties of concrete in addition to aggregate area fraction. The weaker ITZ can significantly decrease the stiffness and increase diffusivity of concrete. The modelling results are expected to guide the design of concrete materials from the perspective of aggregate characteristics.